Evaluation of autonomic cardiac modulation and body composition in elderly submitted to the protocol of exercise and the gametherapy: A clinical trial protocol (SPIRIT compliant). Issue 47 (25th November 2022) - Thoma, Sáskia Fürstenberg; Pérez-Riera, Andrés Ricardo; Silva, Eduardo Antônio Costa; Costa, Ester Laura Cordeiro Oliveira; Ferreira, Airlon Nery; Belfort, Emanuel Ewald Thoma; Leite, Jéssica Costa; Zangirolami-Raimundo, Juliana; Raimundo, Rodrigo Daminello
Abstract : Introduction: Aging affects the cardiovascular system by impairing the amount and strength of cardiac pumping. Heart rate variability (HRV) is a safe parameter to assess variations in the cardiovascular system, providing data on sympathetic and parasympathetic activations. Objectives: Our primary aim is to investigate the cardiac autonomic modulation and body composition of active older adults participating in a physical exercise protocol and gametherapy. Our secondary aim is to assess their functional capacity, cognitive function, balance, respiratory pressures, and functional autonomy. Method: This randomized clinical trial will include 100 active older adults aged 60 to 80 years. The exercise group (EG) will perform 24 supervised training sessions (strength and aerobic) for 12 weeks (2 60-minutes sessions per week). The gametherapy group (GG) will exercise using gametherapy. Assessments will occur on the first week, after the 12th week, after wash out and in the end of cross over. The primary outcome will be HRV and body composition (bioimpedance). Secondary outcomes will be functional capacity (6-minute walk test), cognitive function (mini-mental state examination), risk of falls and balance (berg balance scale and timed up and go test), inspiratory and expiratory pressures (manovacuometry) and functional autonomy (functional reach test and group of Latin American development to maturity [GDLAM] protocol). Discussion: This study will provide relevant information about the effects of physical training (physical exercises and gametherapy) on HRV and other variables in active older adults.